Traditional Banjar games-based physical education for improving physical fitness - Sahbana Ridha; Dewi Fortuna Septiantika; Rika Setyawati; Alpian Husna; Mashud Mashud (Sriwijaya Journal of Sport, 2026)
Research Problem: This study addresses the low level of physical fitness among elementary school students and the limited integration of culturally relevant approaches in Physical Education (PE), which is important due to its impact on students’ health and learning readiness. Research Objectives: This study aims to analyze the effect of integrating traditional Banjar games, namely Baasinan and Tali Ulai, into PE instruction on students’ physical fitness improvement. Methods: This study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The participants were 36 Grade III and IV students (20 males, 16 females) of SD Negeri Banjarbaru, Indonesia, selected through total sampling. Data were collected using the Indonesian Student Fitness Test (TKSI), including the V Sit-and-Reach Test, Half Sit-Up Test, Hand-Eye Coordination Test, T-Test, and Around the World Test. Data were analyzed using a paired sample t-test after fulfilling normality assumptions. Results: The findings showed a significant improvement in students’ physical fitness, with a significance value of .000 (p < .05), and the mean score increased from 12.45 (pretest) to 16.32 (posttest). This indicates that the intervention had a positive effect. Conclusion: The study concludes that integrating traditional Banjar games into PE instruction is effective in enhancing students’ physical fitness. This finding contributes to the development of culturally based PE learning and suggests future research involving larger samples and long-term implementation.